ANALISIS SKALABILITAS APLIKASI SMART PARKING MELALUI PENERAPAN CLEAN ARCHITECTURE - Abdillah, Fauzan; Sirojudin, Achmad; Amin, Muhammad Yusril; Atmadji, Ery Setiawan Jullev (Universitas Methodist Indonesia, 2024)
This research aims to enhance the capabilities of smart parking applications with a focus on scalability, organized structure, and ease of maintenance. We adopt the principles of Clean Architecture to separate functional layers and ensure clear isolation between business logic and specific implementations. The implementation of Clean Architecture in smart parking demonstrates a structured approach with high cohesion and component independence. Tools such as freezed, Dio, and Bloc pattern contribute to the development that is maintainable and extensible. This study provides practical insights into the application of Clean Architecture in real-life scenarios, emphasizing structured features' core and efficient state management with the Bloc pattern. This approach illustrates how Clean Architecture can be effectively applied to achieve scalability, good organization, and ease of maintenance in developing smart parking applications.